Industial Training Report : Ta Ann Holding Berhad Pelitama Sdn. Bhd. Seredeng Oil Palm Plantation / Mohamad Nazeri Hussain - Hussain, Mohamad Nazeri (Universiti Teknologi MARA Cawangan Sarawak, Cawangan Sarawak, 2015)
The training aims to equip the students an introduction to the various aspects in the field of Estate Management .